Autophagy-independent function of Atg1 for apoptosis-induced compensatory proliferation. - Li, M.; Lindblad, J.L.; Perez, E.; Bergmann, A.; Fan, Y. (BMC Biology, 2016)
ATG1 belongs to the Uncoordinated-51-like kinase protein family. Members of this family are best characterized for roles in macroautophagy and neuronal development. Apoptosis-induced proliferation (AiP) is a caspase-directed and JNK-dependent process which is involved in tissue repair and regeneration after massive stress-induced apoptotic cell loss. Under certain conditions, AiP can cause tissue overgrowth with implications for cancer. Here, we show that Atg1 in Drosophila (dAtg1) has a previously unrecognized function for both regenerative and overgrowth-promoting AiP in eye and wing imaginal discs. dAtg1 acts genetically downstream of and is transcriptionally induced by JNK activity, and it is required for JNK-dependent production of mitogens such as Wingless for AiP. Interestingly, this function of dAtg1 in AiP is independent of its roles in autophagy and in neuronal development. In addition to a role of dAtg1 in autophagy and neuronal development, we report a third function of dAtg1 for AiP.